2015
DOI: 10.1063/1.4927734
|View full text |Cite
|
Sign up to set email alerts
|

The gas phase emitter effect of lanthanum within ceramic metal halide lamps and its dependence on the La vapor pressure and operating frequency

Abstract: The gas phase emitter effect increases the lamp lifetime by lowering the work function and, with it, the temperature of the tungsten electrodes of metal halide lamps especially for lamps in ceramic vessels due to their high rare earth pressures. It is generated by a monolayer on the electrode surface of electropositive atoms of certain emitter elements, which are inserted into the lamp bulb by metal iodide salts. They are vaporized, dissociated, ionized, and deposited by an emitter ion current onto the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…differences between the electrode tip temperatures within the two half periods fade away. This is not only the case for an arc current of 800 mA, switched-dc, according to figure 26, but also for an arc current of 500 mA, switched-dc, as is shown in figure 9(a) of [29]. The courses of T tip ( f ), measured within the La and NLa1 lamps, are not very different from the courses of T tip ( f ) in figures 21 and 23, but in the NLa2-lamp, the courses of T tip ( f ) within the anodic and cathodic half period deviate distinctly from the previous ones.…”
Section: 32mentioning
confidence: 65%
See 4 more Smart Citations
“…differences between the electrode tip temperatures within the two half periods fade away. This is not only the case for an arc current of 800 mA, switched-dc, according to figure 26, but also for an arc current of 500 mA, switched-dc, as is shown in figure 9(a) of [29]. The courses of T tip ( f ), measured within the La and NLa1 lamps, are not very different from the courses of T tip ( f ) in figures 21 and 23, but in the NLa2-lamp, the courses of T tip ( f ) within the anodic and cathodic half period deviate distinctly from the previous ones.…”
Section: 32mentioning
confidence: 65%
“…The results have shown that the initial assumption may only be correct in the case of high pressure sodium lamps. Instead, it was found that the emitter effect is based on the cataphoretic transport of metal ions [21][22][23][24][25][26][27][28][29]. Other pyrometric cathode temperature measurements in metal halide lamps with a cylindrical quartz burner confirm the finding [30].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations